In Vitro Efficacy of Tetracyclines Against Multi Drug Resistant Acinetobacter Baumannii Amongst Intensive Care Patients - Muhammad Fayyaz; Hafsa Khalil; Irfan Ali Mirza; Uzma Meral; Humaira Zafar; Wajid Hussain (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the anti-microbial susceptibility and frequency of A.baumannii, especially focusing the efficacy of Doxycycline and Minocycline against multi drug resistant (MDR) and extremely drug resist ant (XDR) A.baumannii in atertiary care hospital.